Evaluation of the Sustainability on Cultural Heritage and Environmental Factors in Architecture from a Tourism Point of View: Ayvalik Historical City Center - Cetiner, Olcay; Gokyilmaz, Aysegul Cetiner (SPRINGER-VERLAG BERLIN, 2011)
Tourism should be evaluated as a sustainable progress tool to obtain the continuity in the areas which acquires cultural heritage and natural values. It is observed that, the two important visual features in tourism are the environmental characteristics and the architectural characteristics of the accommodation buildings that belong to cultural heritage. Environmental protection conception and returning back to nature also affected the architecture. Today, people that have a certain intellectual and cultural level, prefer and look for environmentally interrelated facilities that are peculiar to that district, that are completely in nature, that are providing an interactivity with the local people, and have cultural heritage, rather than facilities that have a common architectural style, that have a good comfort of a luxury hotel and that are indented and self-sufficient. These kinds of facilities are mostly developed by Small Sized Tourism Firms (STF) and Micro Entrepreneurs/Very Small Sized firms. The STF's are obtained from a lot of different source. Most of them are developed by special investors using small capitals. Some others, especially micro entrepreneurs/very small sized firms are mostly owned and ran by a family. In this study, evaluation of the sustainability on cultural heritage and environmental factors in architecture from a tourism point of view and the characteristic features and design approaches of the STF's that are already located in or might be located in Ayvalik historical city center are analysed.
Keywords: Cultural heritage; Environmental factors; Sustainability; Tourism in architecture; Small sized tourism firms; and micro entrepreneurs/very small sized firms; Ayvalik historical city center; Environmental Sciences & Ecology